Song variation in the Chiffchaff Phylloscopus collybita: Song parameters suitable for individual coding - Průchová, Alexandra (Jihočeská univerzita, 2014)
My study deals with general individual characteristics in songs of a passerine bird species Chiffchaff (Phylloscopus collybita), especially I examines the potential of these characteristics for application in acoustic monitoring of bird individuals. I have found that Chiffchaffs have individually distinct songs but unfortunately, song features I measured were not stable in time and hence they would not be suitable for long-term monitoring of individuals. My study suggests that acoustic individual recognition might be challenging in songbird species due to the complexity and plasticity of their song.
Song variation in the Chiffchaff Phylloscopus collybita: Song parameters suitable for individual coding